KESOPANAN MEMINTA MAAF DALAM BAHASA INGGRIS OLEH ORANG JAWA (Studi Kasus pada Orang Jawa Berbahasa Inggris di Surabaya) - , Istianatul Hikmah ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study is a study case of apology politeness used by Javanese who speak English in Surabaya. Bregman and Kasper (1993: 82), apology is a compensation act for the breaking action which is done by the speaker to hearer. This study observes three things those are: (1) How is the classification of apology speech act in English used by Javanese